Penerapan Teknik Kolase Dalam Meningkatkan Kemampuan Seni Rupa Pada Anak Usia 5-6 Tahun Di Kb Az-Zahra Kecamatan Agrabinta Kabupaten Cianjur - Jamilah, Siti; Maulana, Redi Awal; Elnawati, Elnawati (Innovative: Journal Of Social Science Research, 2025)
This study aims to improve fine arts skills of children aged 5-6 years through the application of collage techniques at KB Az-zahra Agrabinta District, Cianjur Regency. The background of this research departs from the results of observations which show that most children have not been able to express themselves, explore materials, or imagine optimally in art activities. This study used the method of Classroom Action Research (CTA) with the Kemmis and McTaggart model which was carried out in two cycles. The research subjects were 25 children in group B. Data collection techniques were carried out through observation, documentation, and assessment of children's work. The results showed that the application of collage techniques was significantly able to improve children's fine arts skills. Collage activities provide stimulation to creativity, fine motor skills, focus, and children's confidence in expressing ideas visually. Thus, the collage technique proves to be effective as a learning method that supports the development of fine arts in early childhood. Keywords: collage technique, fine arts, early childhood, creativity, PAUD.